EU railway policy-making : on track? - Dyrhauge, Helene; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Through policy and intervention national governments in Europe have long held an active interest in railways, an interest that has transferred to the supranational level via the EU commission. This book explores why the EU Commission has been so slow in creating an EU railway policy, pointing the finger at strong resistance by national governments.
Keywords: Political science; Public policy; Europe -- Politics and government; European Union; Globalization; Public administration; Political Science and International Relations; European Union Politics; European Politics